Qur'an Literacy in Children (Phenomenological Study at Um Hafidzah Integrated Islamic Elementary School) (Arfannur: Journal of Islamic Education, 2024)
Al-Qur'an literacy is the ability to develop three main skills in interacting with the Al-Qur'an, these skills are the skills of reading, writing and memorizing the Al-Qur'an. This research aims to analyze the implementation of love for the Qur'an from an early age in children, until a Al-Qur'an literacy program was held at Sd It Ummu Hafidzah, Citarum Village, Kab. Deli Serdang. The focus of the study is on two things, namely the Implementation of Al-Qur'an Literacy in Children and the Usefulness of Al-Qur'an Literacy Methods. The research method used is qualitative based on a phenomenological approach. The information collection methods used were observation, interviews and documentation research. The information obtained was then analyzed using the Miles and Huberman methods, namely information reduction and conclusion drawing. The findings of the analysis show that the Al-Qur'an literacy program can improve students' skills in reading the Al-Qur'an. The pattern applied in this research is that students read the Qur'an together in the school field for 35 minutes and in the classroom. Full support is provided by the entire school community which includes the principal, educators, staff, and external supporting variables originating from the students' own conditions, for example the family in carrying out Al-Qur'an skills training.